Eco-Faith Movement Waste Sorting Movement as a Reflection of Faith and Environmental Morals at MA-Ulya Islamic Centre Bin Baz Yogyakarta - Robbaniyah, Qiyadah; Khoirunnisa, Salsabila; Dzakiyyah, Azzah Husna; Lapandewa, Asmawati; Anggreini, Sari; Hidayanti, Rihar Diannisa (AR-RASYID : Jurnal Pendidikan Agama Islam, 2025)
This study aims to analyze the Eco-Faith Movement through the Waste-Sorting Program as a reflection of faith and environmental ethics at MA-Ulya Islamic Centre Bin Baz Yogyakarta. This movement seeks to integrate Islamic spiritual values with ecological responsibility, positioning waste management not merely as a duty of cleanliness but also as a form of worship and an expression of faith. The research employed a descriptive qualitative approach, utilizing in-depth interviews, participatory observation, and documentation with teachers, administrators, and students involved in the waste-sorting activities. Data analysis followed the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing, with source triangulation used for validation. The findings indicate that the Waste-Sorting Program successfully integrates environmental education with religious practice through habituation and exemplary behavior in students' daily routines. This activity cultivates ecological awareness, discipline, and a sense of responsibility as manifestations of faith in Allah's creation. Beyond improving the cleanliness and comfort of the pesantren environment, the program also fosters a circular economy system by managing waste with economic value. Overall, the Eco-Faith Movement at MA-Ulya Islamic Centre Bin Baz serves as a concrete model of environmentally-based Islamic education that nurtures religious character while encouraging care for environmental sustainability.